2017
DOI: 10.4081/mm.2017.6614
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of enteric and systemic Yersinia enterocolitica infection in a chronic, not iron-overloaded dialysis patient

Abstract: SummaryWe present herein a case of bacterial gastroenteritis due to Yersinia enterocolitica, occurred in a young woman undergoing haemodialysis with a previous history positive for prolonged (20 years) immunosuppressive therapy for glomerulonephritis before and for kidney transplant later. The patient's outcome was favourable after a third-generation cephalosporin treatment without complications. The possible pathophysiological association between patient clinical condition and Yersinia bacteraemia is discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Although the incidence is very low [15], it is a serious problem due to a death rate of about 30% [23,24]. It is necessary to apply antibiotic therapy when a generalised infection is diagnosed [6]. In our case report, the bacterial strain was sensitive to most of the antibiotics applied.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Although the incidence is very low [15], it is a serious problem due to a death rate of about 30% [23,24]. It is necessary to apply antibiotic therapy when a generalised infection is diagnosed [6]. In our case report, the bacterial strain was sensitive to most of the antibiotics applied.…”
mentioning
confidence: 68%
“…Yersinia spp. may cause severe illness in patients with immunodeficiency [6,7], like in the case of a patient with pemphigus foliaceus who developed sepsis. Recent observations have shown that the percentage of generalised infections caused by Yersinia spp.…”
mentioning
confidence: 99%
“…Most HD patients infected by YE were found to be overloaded with Fe (52)(53)(54)(55). However, there is also a report of an HD patient infected with YE without being overloaded with Fe (56). Some studies have suggested that ESA therapy might help in the treatment of YE, as it lowers serum ferritin and transferrin saturation, and improves phagocytosis (57)(58)(59).…”
Section: Incidence and Prevalence Of Ye Infection In Dialysis Unitsmentioning
confidence: 99%
“…Septicemia due to YE infection has been reported sporadically. Some reported cases were associated with the administration of deferoxamine (60-62), and one case was reported due to eating undercooked meat (56). Table 1 summarizes the reported YE infections in HD patients.…”
Section: Incidence and Prevalence Of Ye Infection In Dialysis Unitsmentioning
confidence: 99%